Widths and best approximations for classes of convolutions of periodic functions - Serdyuk, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish exact lower bounds for the Kolmogorov widths in the metrics ofC andL for classes of functions with high smoothness; the elements of these classes are sourcewise-representable as convolutions with generating kernels that can increase oscillations. We calculate the exact values of the best approximations of such classes by trigonometric polynomials.